553 Assessment of sleep disorders in children and adolescents with obesity. (3rd May 2021) - Zarpellon, Raquel Simone Maccarini; Vilela, Regina Maria; Radominski, Rosana Bento; de Souza Crippa, Ana Chrystina
Abstract: Introduction: When studying the inherent aspects of sleep it is important to assess how the quality and quantity of sleep in the last two decades may be one of the reasons for the increase in childhood obesity, which has been growing rapidly worldwide. This study aims to assess the presence of sleep disorders in overweight children and adolescents. Methods: An descriptive study was conducted with data collection from 43 patients between 6 and 13 years old diagnosed as overweight. They were patients of a specialized service for children and adolescents with obesity that is part of the Hospital de Clínicas of the Federal University of Paraná, located in Curitiba, Brazil. To investigate the presence of sleep disorders, the Sleep Disturbance Scale for Children (SDSC) questionnaire was administered. The factors assessed were: Disorders of Initiating and Maintaining Sleep, Sleep Breathing Disorders, Disorders of Arousallnightmures, Sleep Wake Transition Disorders, Disorders of Excessive Somnolence and Sleep Hyperhydrosis. Results: The mean age of the patients that took part in the research was 10 years and 7 months (± 1.95). The mean BMI of the participants was 29.57 kg/m2 (± 4.38), the majority being diagnosed with obesity. The sum of all SDSC factors demonstrated the presence of pathological sleep in 58.1% (25) of the sample, whereas 51.2% (22) of the patients had Sleep Breathing Disorders and 58.1% (25) had the Sleep Wake Transition Disorder. Conclusion: The present study demonstrated the presence of sleep disorders in overweight children and adolescents. As for Sleep Respiratory Disorder, a situation has already been advocated in the current literature for this audience. In relation to the Sleep-Wake Transition Disorder and pathological sleep, further research is needed to prove the presence of the disorder in other groups studied. Here is the suggestion that future research be done with subjective and objective data collection on sleep within a larger sample, in order to confirm the association between sleep disorders and childhood obesity. Support (if any):